24/7 TIA-service - van Rooij, Frank G (Igitur publishing, 2012)
Although the symptoms of a transient ischemic attack (TIA) by definition resolve completely, the subsequent risk of cardiovascular complications is substantial. Urgent diagnosis and start of secondary prevention can reduce these risks. In light of the potential unfavourable prognosis, especially the first days after a TIA, we have developed and implemented a 24/7 TIA-service. Patients can be referred at any time and timing of analysis is determined by means of short-term risk assessment with a validated tool. Within half a day all investigations necessary to diagnose TIA and identify risk factors take place and secondary prevention at all levels is started immediately. This service is realized through integration of workflow of different specialities at multiple levels of care. Although patient service improves, the beneficial effects of a 24/7 TIA-service need to be established before further implementation is started. A preliminary analysis on the effects of continuous TIA-care and suggestions for the development of the necessary process and outcome indicators are provided.